Behavioural responses of non-breeding waterbirds to drone approach are associated with flock size and habitat. Issue 2 (2nd April 2020) - Jarrett, David; Calladine, John; Cotton, Anne; Wilson, Mark William; Humphreys, Elizabeth
ABSTRACT: Capsule: Non-breeding waterbirds are more likely to respond to drone approach when in larger flocks, and responses are more likely in arable and coastal habitats than at inland lochs. Aims: To investigate the extent to which drones are a potential source of disturbance to non-breeding waterbirds. Methods: Using a commercially available quadcopter drone, we approached waterbird flocks of varying sizes in coastal, freshwater, and arable habitats following a standardized protocol. Results: Waterbirds at coastal sites and in arable fields were more likely to respond to drone approach than those at inland freshwater bodies. Larger flocks were more likely to respond to drone approach and responded at a greater distance than smaller flocks. Conclusion: Repeated drone use at coastal and arable sites with large aggregations of feeding or roosting waterbirds could cause energetically costly flight responses, increased stress, and effective loss of available habitat. At such sites, it may be beneficial to regulate recreational and commercial drone use to minimize potential disturbance effects.